Analyzing International Research Impact of Korean Kinesiology Articles - Danielle Lee (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to explore and analyze research impact of Korean 'Kinesiology' studies, especially in the aspects of international research impact gauged by the citation counts from Scopus bibliometric database. This study contributes to relevant literature in that it is the first endeavour to evaluate the pattern about how the entire Korean 'Kinesiology' articles have been cited in international articles. METHODS TTwo types of sample articles were collected in this paper. Firstly, 19,867 target articles published in 23 KCI-accredited Korean 'Kinesiology' related journals from 2001 to 2015. For the Korean target articles, secondly, international citing articles that took advantage of target articles as references were collected from Elsevier's Scopus database separately. RESULTS As a result, just 5% of the target articles were cited at least once for five years after publication. The topics of top cited research topics include 'exercise', 'physical activity,' 'Alzheimer's disease, ' 'body composition' and 'insulin resistance'. Besides, the Korean 'Kinesiology' articles were the most influential to articles about 'Medicine,' 'Health Professions,' 'Multidisciplinary,' 'Social Sciences,' and 'Nursing'. CONCLUSIONS This study showed that one Korean 'Kinesiology' article was cited 0.09 times on an average in international Scopus-indexed articles. Considering that the average number of citations in domestic articles is 5.6 times, the international citations of Korean 'Kinesiology' research still have much room for growth. However, this study confirmed that the scope of the international impact is not limited to a few countries, but is spreading to various countries, and its impact has been growing in recent years.